2010
DOI: 10.1021/ja910762q
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Resonance Levels and Nanostructuring in the PbTe−CdTe System and Enhancement of the Thermoelectric Figure of Merit

Abstract: We explored the effect of Cd substitution on the thermoelectric properties of PbTe in an effort to test a theoretical hypothesis that Cd atoms on Pb sites of the rock salt lattice can increase the Seebeck coefficient via the formation of a resonance level in the density of states near the Fermi energy. We find that the solubility of Cd is less than previously reported, and CdTe precipitation occurs to create nanostructuring, which strongly suppresses the lattice thermal conductivity. We present detailed charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
138
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 172 publications
(149 citation statements)
references
References 39 publications
9
138
1
1
Order By: Relevance
“…This value matches perfectly the result given recently in Ref. [11]. The remaining Cd is still present in investigated sample but not as a constituent of the crystal phase (solid solution) but in the form of nanoclusters or small liquid droplets, which cannot be detected in the X-ray diffraction experiment (one has to mention that for bulk Cd the melting temperature is equal to T = 594 K but for Cd in the form of nanoclusters this temperature should be significantly smaller).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This value matches perfectly the result given recently in Ref. [11]. The remaining Cd is still present in investigated sample but not as a constituent of the crystal phase (solid solution) but in the form of nanoclusters or small liquid droplets, which cannot be detected in the X-ray diffraction experiment (one has to mention that for bulk Cd the melting temperature is equal to T = 594 K but for Cd in the form of nanoclusters this temperature should be significantly smaller).…”
Section: Resultssupporting
confidence: 93%
“…These results did not confirm the solubility limit known from the literature and suggested the necessity of some correction of the relevant phase diagram. Very recently, our findings were confirmed in part by the value of the solubility limit x < 0.01 [11], which was much lower than that suggested previously.…”
Section: Introductionsupporting
confidence: 84%
“…30). High zT was also found by different studies in PbTe-MTe 31-34 (M: Ca, Mg, Sr, Ba) and PbTe-CdTe, 35,36 where they were shown to have nano-scale features that are also suggested as important for good thermoelectric properties. For the less studied chalcogenides, high zT was also reported for systems such as PbSe-PbS, 37 PbSe-MSe [38][39][40] (M: Ca, Sr, Ba), and PbS-XS 41,42 (X: Ca, Sr, Zn, Cd), where similar nanostructures were also observed.…”
Section: Introductionmentioning
confidence: 59%
“…These are behaviors of solid solutions with statistically random atomic distribution. Recently many lead chalcogenides [31][32][33]35,36,39,[48][49][50][51] (including PbSe with PbS addition < 16%) are found with nanostructures on the <10 nm scale using TEM. These features on the nanoscale are not necessarily in conict with our SEM observation at larger scales.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, we prepared Nb-doped SrTiO 3 composites by adding nanostructured yttria stabilized zirconia (YSZ) 8) and mesoporous silica (MS) 9) by the pressure-less sintering method. These additions could effectively reduce thermal conductivity by enhancing phonon scattering at grain boundaries and increase the electrical conductivity by promoting densification, and then enhanced the ZT value, which strongly triggered our interest to investigate other effective nanosized additions to further enhance the thermoelectric properties of Nbdoped SrTiO 3 .…”
Section: Introductionmentioning
confidence: 99%